Analysis of As Sab’ad Islamic Boarding School Culture in Improving Student's Moral Action - Ratnasari, Wahyu Nur; Ezif Rizqi Imtihana (AT-TAJDID: Journal of Islamic Education, 2026)
This study aims to investigate in depth the impact of Assabad Islamic Boarding School on the moral development of students at MA Muhammadiyah 01 Tegalombo. This study uses a qualitative approach involving interviews, observations, and document analysis as data collection techniques. The main participants in this study were students, teachers, and staff of Assabad Islamic Boarding School who are directly involved in the Islamic education process at MA Muhammadiyah 01 Tegalombo. Data were collected through in-depth interviews with participants, direct observations of activities at the Islamic boarding school and school, and document analysis related to the curriculum, extracurricular activities, and moral development programs carried out by the boarding school. The results show that Assabad Islamic Boarding School has a positive impact on the moral development of students at MA Muhammadiyah 01 Tegalombo. The boarding school makes a significant contribution in shaping the moral, ethical, and spiritual character of students through a holistic learning approach integrated with Islamic values. In addition, the boarding school also provides space for students to develop social skills, leadership, and empathy through various extracurricular activities and development programs.